Fenomena Sosial Remaja Hamil Diluar Nikah Ditinjauh Dari Aspek Hukum Adat Desa Legu Woda Kecamatan Magepanda - Afrino Aryanto Wae; Danar Aswim; H.Rodja Abdul Natsir (International Forum of Researchers and Lecturers, 2023)
. This study aims to determine social phenomena and how the views of customary law on early adolescents who are pregnant out of wedlock in Legu Woda Village, Magepanda District, Sikka Regency. This type of research is qualitative. To collect data, research uses interview techniques, observation and documentation. The data analysis technique used is data reduction, data presentation, and drawing conclusions. Based on this research, it can be concluded that teenage pregnancies out of wedlock are caused by factors that influence them, including technological, educational and social factors of children in the environment where they are. Lack of knowledge and understanding often makes children unable to choose for a good or bad life in the future. with social conditions that are often judged by the community, so that if a teenage child becomes pregnant out of wedlock, they will be ostracized and become the talk of the community. So that in social life, of course, there are rules regarding the norms of life that apply, one of which is customary law. Customary law and society cannot be separated because it is a reciprocal relationship. The views of customary law or traditional leaders Legu Woda (lio) on teenage pregnancies out of wedlock if the teenage child is found to be pregnant, the first thing to do is to find out who the father of the child is and if it is known, then the woman's family is asked to be responsible for male family. This is so that action can be taken immediately in accordance with applicable customs.